2018
DOI: 10.1002/jia2.25124
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of HIV self‐testing and linkage to treatment among men who have sex with men (MSM) in Nigeria: A pilot programme using key opinion leaders to reach MSM

Abstract: Introduction HIV self‐testing (HIVST) offers an alternative to facility‐based HIV testing services, particularly for populations such as men who have sex with men (MSM) who may fear accessing testing due to stigma, discrimination and criminalization. Innovative HIV testing approaches are needed to meet the goal of 90% of people living with HIV being diagnosed. This study piloted an intervention to distribute oral HIVST kits to MSM through key opinion leaders (KOLs) in Lagos, Nigeria and assessed the feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(134 citation statements)
references
References 46 publications
3
128
3
Order By: Relevance
“…Tun et al . present the results of a pilot intervention to distribute oral HIV self‐testing kits to MSM through key opinion leaders in Lagos, Nigeria . This study found that not only is oral self‐testing feasible and highly acceptable among MSM in this urban population, but also that effective linkage to treatment can be achieved for those who test positive through self‐testing with active follow‐up and access to a trusted MSM‐friendly community clinic that offers HIV treatment.…”
Section: Innovations In Hiv Testing Modalities and Linkage To Treatmentmentioning
confidence: 96%
“…Tun et al . present the results of a pilot intervention to distribute oral HIV self‐testing kits to MSM through key opinion leaders in Lagos, Nigeria . This study found that not only is oral self‐testing feasible and highly acceptable among MSM in this urban population, but also that effective linkage to treatment can be achieved for those who test positive through self‐testing with active follow‐up and access to a trusted MSM‐friendly community clinic that offers HIV treatment.…”
Section: Innovations In Hiv Testing Modalities and Linkage To Treatmentmentioning
confidence: 96%
“…Successful linkage rates to HIV confirmatory testing and antiretroviral therapy (ART) among MSM who tested reactive by HIV self‐testing were reported in a range of 31% to 100% from studies conducted in resource‐limited and high‐income countries . Factors associated with unsuccessful linkages to HIV confirmatory testing and/or ART, however, have not been extensively explored due to a survey nature of studies and/or small number of MSM participants who tested reactive by HIV self‐testing.…”
Section: Introductionmentioning
confidence: 99%
“…A low number of the participants called through the helpline. This was expected, since most the respondents found the instructions easy to use to understand and use [17]. Other studies have also shown signi cantly low usage of the hotlines [18].…”
Section: Discussionmentioning
confidence: 52%
“…Hence the MSM who feel generally "healthy" though sero-positive but with no sign and symptoms are likely not to link to care. A study conducted in Nigeria among the MSM community showed a 100% linkage to HIV and treatment [17]. The high linkage in that study was likely due to follow-up calls after HIVST distribution, the ease of participant's access to the opinion leaders and also the linkage to a well-trusted MSM-friendly facility that offers HIV prevention services.…”
Section: Discussionmentioning
confidence: 87%